1997
DOI: 10.1021/bp9700014
|View full text |Cite
|
Sign up to set email alerts
|

Glass Transition and Thermal Stability of Lactase in Low‐Moisture Amorphous Polymeric Matrices

Abstract: The thermal stability of a commercial preparation of neutral lactase ( -galactosidase) in low-moisture amorphous polymeric matrices of maltodextrin (MD dextrose equivalent (D.E.) ) 10.9) and polyvinylpyrrolidone (PVP; MW 40 000) stored at various temperatures (T) was studied. The main objective was to analyze the usefulness of the glass transition temperature (T g ) as a parameter for predicting the thermal stability of lactase in low-moisture glass-forming matrices. Loss of enzyme activity was observed during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 29 publications
2
23
0
1
Order By: Relevance
“…Variations in chemical stability that do not seem to be related to global mobility have also been observed for various solid proteins, including restriction enzyme EcoRI dried with sucrose, trehalose, maltodextrin or PVP, 104 lactase and invertase lyophilized with trehalose, maltose, lactose, sucrose, raffinose, maltodextrin, casein or PVP, 22,[105][106][107][108] and glucose-6-phosphate dehydrogenase lyophilized with dextran, sucrose or raffinose. [109][110] It is not easy to explain the lack of correlation between chemical stability and global mobility for proteins because of many complicated factors possibly affecting the chemical stability.…”
Section: Examples For Chemical Stability Not Apparently Related To Glmentioning
confidence: 96%
“…Variations in chemical stability that do not seem to be related to global mobility have also been observed for various solid proteins, including restriction enzyme EcoRI dried with sucrose, trehalose, maltodextrin or PVP, 104 lactase and invertase lyophilized with trehalose, maltose, lactose, sucrose, raffinose, maltodextrin, casein or PVP, 22,[105][106][107][108] and glucose-6-phosphate dehydrogenase lyophilized with dextran, sucrose or raffinose. [109][110] It is not easy to explain the lack of correlation between chemical stability and global mobility for proteins because of many complicated factors possibly affecting the chemical stability.…”
Section: Examples For Chemical Stability Not Apparently Related To Glmentioning
confidence: 96%
“…1 It has been suggested that below this temperature the high viscosity of the unfrozen glassy phase and the low diffusion coef®cients of species within this matrix provide conditions that lead to a marked decrease in the rate of reactions associated with food deterioration. 2 However, recent kinetic studies of chemical processes such as non-enzymatic browning, 3±5 oxidation of ascorbic acid, 6±8 enzymatic reactions, 9±12 colour stability, 13 aspartame degradation, 14 lactase stability, 15 starch retrogradation 16 and lipid oxidation 17 have produced results both for and against the importance of T g and the Williams± Landel±Ferry (WLF) kinetics associated with the expected changes in viscous properties.…”
Section: Introductionmentioning
confidence: 99%
“…Although thermal stability of enzymes is expected to be related to mobility aspects, the influence of glass transition has not yet been fully demonstrated and the specific mechanism of enzyme protection observed in trehalose matrices can not be attributed entirely to the glass transition phenomenon (3). The extent of protection provided by poly(vinyl)pyrrolidone (PVP) and maltodextrin (MD) matrices on the thermal stability of invertase (3) and lactase (13) is somewhat related to their glass transition temperatures. However, even when the matrices are in the glassy state, the loss of enzymatic activity is important if the temperature is sufficiently high (3,13).…”
Section: Introductionmentioning
confidence: 99%
“…The extent of protection provided by poly(vinyl)pyrrolidone (PVP) and maltodextrin (MD) matrices on the thermal stability of invertase (3) and lactase (13) is somewhat related to their glass transition temperatures. However, even when the matrices are in the glassy state, the loss of enzymatic activity is important if the temperature is sufficiently high (3,13). Cardona et al (14) demonstrated that if sufficient water was present to allow crystalline trehalose dihydrate formation in a high proportion, the protective action of trehalose on invertase stability was lost.…”
Section: Introductionmentioning
confidence: 99%